Diagnosis of Peste des Petits Ruminants in Wild and Domestic Animals in Xinjiang, China, 2013–2016. Issue 6 (18th January 2017) - Li, J.; Li, L.; Wu, X.; Liu, F.; Zou, Y.; Wang, Q.; Liu, C.; Bao, J.; Wang, W.; Ma, W.; Lin, H.; Huang, J.; et al.
Summary: Peste des petits ruminants viruses (PPRVs) re‐emerged in China at the end of 2013 and then spread rapidly into 22 provinces through movement of live goats and sheep. In this study, 96 samples of domestic animals and 13 samples of wildlife were analysed for the presence of PPRV infection by ELISA or RT‐PCR. Of 96 samples from sheep and goats, 91 were PPRV positive, whereas all of the 13 samples from three wild species, Capra ibex ( Capra ibex sibirica ), argali ( Ovis ammon ) and Goitered gazelle ( Gazella subgutturosa ), were found to be positive. Five wildlife‐origin isolates from the above samples were identified as the lineage IV by a multiple alignment of the partial sequences in N gene.